2015
DOI: 10.1016/j.microrel.2015.06.097
|View full text |Cite
|
Sign up to set email alerts
|

Study of short-circuit robustness of SiC MOSFETs, analysis of the failure modes and comparison with BJTs

Abstract: International audienceThis paper presents experimental robustness tests made on Silicon Carbide (SiC) MOSFETs and SiC Bipolar Junction Transistors (BJTs) submitted to short-circuit operations (SC) or current limitation modes. For SiC MOSFETs, a gate leakage current is detected before failure without being responsible for the immediate failure. Nevertheless this gate leakage current is not without effect on the integrity of the SiC MOSFETs. Based on several robustness tests performed on SiC MOSFETs and on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
36
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 6 publications
1
36
0
Order By: Relevance
“…Recently, several research efforts demonstrate that ruggedness of SiC power MOSFETs during short-circuit (SC) is, for most of devices, much lower than silicon (Si) devices, with similar rating [1]. Indeed, the weakness may be related to a higher short-circuit current density and a lower die area resulting in a higher temperature rising during SC leading to faster degradations.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, several research efforts demonstrate that ruggedness of SiC power MOSFETs during short-circuit (SC) is, for most of devices, much lower than silicon (Si) devices, with similar rating [1]. Indeed, the weakness may be related to a higher short-circuit current density and a lower die area resulting in a higher temperature rising during SC leading to faster degradations.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, when operating under these conditions, a lot of energy is dissipated in the device over a short period of time, causing a great increase of temperature in the oxide, favouring gate current increase. This is evidenced by Chen et al [29], who observed an increase in the gate-source current before failure happened during a shortcircuit test and relate this with tunneling current. However, a recent study [3] suggests that Schottky emission may be the predominant phenomenon in this gate current increase.…”
Section: Introductionmentioning
confidence: 81%
“…Many efforts have been devoted to the short-circuit testing of power semiconductor devices. The minimum dissipated energy that leads to failure of the specific device after a single short-circuit is referred to the critical energy E C [7]. If the dissipated energy is less than E C , the device is able to survive after Repetitive Short-Circuit (RSC) testing.…”
Section: Introductionmentioning
confidence: 99%
“…The aim of RSC testing is to study how safe short-circuit operation will affect the electro-thermal parameters and the degradation of power semiconductors, or to benchmark the short-circuit robustness of different devices. Various research activities on RSC testing of Si IGBTs and MOSFETs, and SiC MOSFETs have been presented in [7]- [15]. In [8], the RSC testing of a 600 V customized IGBT module is performed, with a measured saturation current of around 50-60 A.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation